2010
DOI: 10.1128/aac.00512-10
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic-Pharmacogenetic Study of Nevirapine in HIV-Infected Cambodian Patients

Abstract: The aims of this ANRS12154 open-label, single-center, multiple-dose pharmacokinetic study were to characterize nevirapine pharmacokinetics in a Cambodian population of HIV-infected patients and to identify environmental and genetic factors of variability, focusing on the CYP2B6, CYP3A5, and ABCB1 (MDR1) genes. A total of 170 Cambodian HIV-infected patients were included. Nevirapine trough concentrations were measured after 18 and 36 months of starting antiretroviral treatment and in samples drawn during a dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 48 publications
7
44
2
1
Order By: Relevance
“…Data and specimens for these pharmacokinetic analyses were from individuals who had participated in two previously published studies (17,18). This analysis was approved by the Na-tional Ethics Committee of Cambodia and by the Vanderbilt University Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data and specimens for these pharmacokinetic analyses were from individuals who had participated in two previously published studies (17,18). This analysis was approved by the Na-tional Ethics Committee of Cambodia and by the Vanderbilt University Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis was approved by the Na-tional Ethics Committee of Cambodia and by the Vanderbilt University Institutional Review Board. Plasma samples were from 10 healthy, HIVnegative African Americans (group A) who had received a single 200-mg oral dose of nevirapine (17) and from 10 HIV-infected Cambodians (group B) from the ESTHER (Ensemble pour une Solidarité Thérapeu-tique en Réseau) at the Calmette Hospital (Phnom Penh, Cambodia) (18). In both groups, plasma was kept frozen until analysis, and genotype data for CYP2B6 *1*6 were available from the previous studies (17,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ces études ont exploré des aspects fondamentaux de la co-infection VIH-tuberculose : rôle des sous-populations lymphocytaires T et NK (natural killer) dans la physiopathologie et la prédiction du syndrome inflammatoire de reconstitution immunitaire (IRIS) tuberculeux (ANRS 12153 CAPRI NK [7] et ANRS 12164 CAPRI T), variabilité pharmacocinétique et polymorphisme des cytochromes P450 dans une population de patients cambodgiens infectés par le VIH et traités par névirapine ou efavirenz [8] (ANRS 12154 PECAN) et, enfin, diversité génétique de la tuberculose et impact sur la mortalité et l'expression clinique de la tuberculose (ANRS 12278).…”
Section: Les éTudes Associéesunclassified
“…Several studies have reported that the polymorphisms 516G>T and 983T>C in the CYP2B6 gene are associated with variations in NVP pharmacokinetics in ethnically diverse populations [32][33][34][35][36], although the clinical impact remains uncertain since an association between greater NVP exposure and toxic effects has not been fully demonstrated.…”
Section: Cyp2b6-g516gg (Common Genotype)mentioning
confidence: 99%